The quantitative classification of granites and their metallogenetic relations in West Qinling, Gansu Province, China. Issue 1 (2nd January 2019) - Wang, Yuxi; Wang, Xiaowei; Luo, Jianmin; Zhang, Yu; Wang, Jun
ABSTRACT: The quantitative classification of granite and their metallogenetic relations have never been discussed. The Q-system clustering analysis and discriminant analysis methods were alternately used to quantitatively analyze the 11 oxide data in granite samples from the West Qinling area of Gansu Province, and then to construct the quantitative classification series models of granite (oxide). The granites samples are divided into three categories and eight sub-categories. The classification of granites is biased toward prospecting. According to the spatial correlation between eight types of granites and copper deposits, lead and zinc deposits, gold deposits, etc. (within 3 km of the intrusion) in the West Qinling area in Gansu Province, the "metallogenic related intrusions" are sought, and the prospecting target areas are defined. Furthermore, they provide reliable basis for regional geological prospecting.